Strategy for Improving Teacher Quality: Integrating Competence, Professionalism, and Incentives to Enhance Teaching Performance - Prananda, Gingga (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to analyze the strategy for improving teacher quality through the integration of competence, professionalism, and incentives in order to enhance teaching performance. The method used is a literature review, which examines various theories, policies, and previous research related to the topic. The results of the literature review show that high teacher competence, developing professionalism, and appropriate incentives can mutually support each other to improve teacher performance. The integration of these three elements has been proven to create a more effective learning environment, where teachers are more motivated and committed to self-development and the quality of teaching. Policies such as Teacher Certification, although providing significant incentives, need to be balanced with ongoing training and non-financial recognition to motivate teachers more comprehensively. In conclusion, the integration of competence, professionalism, and incentives is an effective strategy for improving teacher quality, but the challenges in implementation on the ground, especially in areas with limited resources, still need to be addressed through more inclusive and equitable policies.